2013
DOI: 10.1113/expphysiol.2013.074971
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gap junction network complexity on pulmonary artery smooth muscle reactivity in normoxic and chronically hypoxic conditions

Abstract: New Findings r What is the central question of this study?Experimental results on intrapulmonary arteries indicate that the relationship between gap junctional intercellular communication and its functional involvement in tissue reactivity is very complex, both in normoxic and in chronically hypoxic conditions. The relationship between the gap junction network and vasoreactivity is poorly known and needs to be explored, including theoretical modelling approaches. r What is the main finding and its importance?O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
6
0
1
Order By: Relevance
“…175 Studies in mice demonstrated that chronic exposure to hypoxia increased the pulmonary arterial constriction induced by depolarizing high potassium solutions. 176,177 This increased potassium sensitivity could be prevented by gap junction inhibitors. A very interesting mathematical model developed on the basis of these findings suggests that not the number of gap junctions per se, but differences in their arrangement could explain this behaviour.…”
Section: Signal Exchange Within Smooth Musclementioning
confidence: 99%
See 1 more Smart Citation
“…175 Studies in mice demonstrated that chronic exposure to hypoxia increased the pulmonary arterial constriction induced by depolarizing high potassium solutions. 176,177 This increased potassium sensitivity could be prevented by gap junction inhibitors. A very interesting mathematical model developed on the basis of these findings suggests that not the number of gap junctions per se, but differences in their arrangement could explain this behaviour.…”
Section: Signal Exchange Within Smooth Musclementioning
confidence: 99%
“…A reduction of the complexity of smooth muscle interactions, possibly induced by hypoxia, might increase the constrictor response of the pulmonary vascular wall since single, "overreacting" cells might act then as effective pacemakers. 177 Gap junctional communication between smooth muscle cells can also lead to conducted responses. In smooth muscle, both smooth muscle-conducted constriction and dilation in response to local application of high potassium or adenosine have been described by de Wit.…”
Section: Signal Exchange Within Smooth Musclementioning
confidence: 99%
“…Таким образом, при хронической гипоксии, хотя уровень NO 2 и NO 3 в плазме крови остаётся выше, усиленное образование эндотелина-1 при ХГГ стимулирует образование свободных радикалов кислорода [2,9], тормозящих реализацию NO своих вазодилатационных влияний на гладкомышечные клетки сосудистой стенки. Это приводит к нарушению равновесия вазоконстриктивных и вазодилатационных влияний со стороны эндотелия на тонус сосудов с доминированием вазоконстриктивных, прежде всего в результате повышенного уровня эндотелина-1 при хронической гипоксии.…”
Section: теоретическая и клиническая медицинаunclassified
“…The electrical and biochemical properties of gap junction channels are regulated by phosphorylation and dephosphorylation of Cxs (12). It has been shown that GJs in pulmonary vascular wall are important for its remodeling and reactivity changes under chronic hypoxia (5,22) and MEGJs are involved in the sustained HPV development in rodent models (30,49). However, such a contribution of GJs to the sustained HPV phase in BIPAs is not yet reported.…”
mentioning
confidence: 99%